MITI and the Japanese miracle : The growth of industrial policy, 1925-1975 - Johnson, Chalmers (Stanford University Press, 1982)
The book analyzes the role of Japan's Ministry of International Trade and Industry (MITI) in shaping economic growth from 1925 to 1975. Johnson examines how industrial policy, state guidance, and government-business relations contributed to Japan's postwar economic miracle and transformed it into a major industrial power.